EFEKTIVITAS METODE DEMONTRASI TERHADAP KETERAMPILAN SISWA DALAM PERAWATAN JENAZAH KELAS XII DI SMK AL FUTUH TIKUNG LAMONGAN - Hasyim; Fitriyah, Hidayatul (Fakultas Agama Islam Universitas Billfath, 2020)
This research is motivated by the low learning outcomes of students in the use of learning methods. The purpose of this study was to determine the effectiveness of demonstration methods on students' skills in caring for the XII class of SMK Al Futuh Tikung. This research uses quantitative research methods, the research design is Quasi Experimental Type Nonequivalent Control Group Design, the research design has a control group and an experimental group. Based on the results of the study showed that